HUBUNGAN POWER OTOT TUNGKAI DENGAN KEMAMPUAN AKURASI SHOOTING PADA PERMAINAN SEPAK BOLA SISWA SMAN 1 LAWA - Ahmad Risal; Hasanuddin Jumareng; Badaruddin (Journal Olympic (Physical Education, Health and Sport), 2022)
The purpose of this study was to determine the relationship between leg muscle power and shooting accuracy in the soccer game of SMAN 1 Lawa students. The population in this study was the total number of class XI students of SMAN 1 Lawa, amounting to 210 people using purposive random sampling technique. The data of this study were analyzed using the statistical technique of 0.05% product moment. In the study, it was concluded that there was a relationship between leg muscle power and shooting accuracy in the soccer game of SMAN 1 Lawa students, where Rxy = 0.48> r table 0.361. While the coefficient of determination (r^2) = 0.24 or 24%. This shows that the level of correlation between the variable leg muscle power (X) and shooting accuracy in the soccer game of SMAN 1 Lawa students (Y) is at a moderate correlation. Besides, 76% is influenced by elements of other physical conditions. The results of this study indicate that there is a significant relationship between leg muscle power and shooting accuracy in the soccer game of SMAN 1 Lawa students.